The Effect of Gamification on Purchase Decisions: Mediation of Customer Experience and Customer Brand Engagement - Barida Rakhma Nuranti; Ayu Diana Ansori; Viant Anggi Saputra; Reska Anggara Putra; Andhika Adhi Nugroho; Listya Shafa Widiyanti; Wiwit Lestari (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of gamification on purchase decisions, mediated by customer experience and customer brand engagement, among users of the "Indomaret Saku" platform in Yogyakarta. This research adopts a quantitative approach with primary data collected through a comprehensive questionnaire using a 5-point Likert scale. The population comprises users of the Indomaret Saku application in Yogyakarta, with a final sample of 166 respondents selected through purposive sampling techniques based on specific criteria including age range, application usage frequency, and geographical location. Data analysis was performed using the Partial Least Squares (PLS) method with SmartPLS 3.0 software, enabling rigorous testing of the proposed structural model. The results demonstrate that gamification exerts a positive and significant effect on both customer experience and customer brand engagement. Furthermore, the analysis confirms that customer experience and customer brand engagement significantly mediate the relationship between gamification and purchase decisions, highlighting the complex psychological mechanisms through which game elements influence consumer behavior in digital platforms.